(untitled) (Tempo e Argumento, 2022)
This article aims to analyze the role that European film festivals played in the articulation of a solidarity network for the victims of the Chilean dictatorship in the first years after the 1973 coup d’état. Through a transnational perspective and in dialogue with festival studies, the text examines the complexity of the links between Latin American political cinema and the film meetings that took place in Europe since the previous decade, focusing on the "long" 1968, a period marked by aesthetic, discursive and institutional renewal that changed the nature of European festivals. In this way, the presence of films, film agents, other public figures, critics, audiences, protest statements, press coverage, among other aspects that make up a festival is analyzed as part of a broader phenomenon of rapprochement between Latin America and Europe around the notion of solidarity and engagement in "Third Worldist" agendas. The article studies the presence of the Chilean cause in three specific festivals, taken as case studies: the Pesaro International New Cinema Festival, the Cannes Film Festival, and the Leipzig International Documentary Film Festival. These meetings present different degrees of centrality in the festival circuit and are located in different countries/blocks of influence zones, which allows us to understand the complex flows that have been established in the solidarity networks. Keywords: festival; Chile; dictatorship; solidarity.